Pengaruh Harga, Kualitas Produk, Diskon Dan Kualitas Pelayanan terhadap Keputusan Pembelian dengan Word of Mouth Sebagai Variabel Moderating pada Toko Mustika Hijab - Nur Ahmadi Bi Rahmani; Juliana Nasution; Sucita Alfiani (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
Business competition and the development of Muslim fashion are currently so rapid in Indonesia along with increasing business competition, consumers are increasingly careful in choosing products, meaning that stores must create creative innovations. This research was conducted using a quantitative approach by considering four independent variables, namely price (X1), product quality (X2), discounts (X3), and service quality (X4). Then one moderating variable, namely Word of Mouth (Z). The sample of this study consisted of 84 people who had bought goods at Mutsika Hijab Stores. The data for this study were collected through primary methods through questionnaires. Data analysis techniques used include validity, reliability and classic assumption tests, as well as hypothesis testing and MRA testing. The results of the study found that price had a positive effect on purchasing decisions, while product quality, discounts and word of mouth had no significant effect. Service Quality, on the other hand, was found to have a positive effect on purchase decisions. Keywords: Price, Product Quality, Discount, Service Quality, Purchasing Decision, Word of Mouth.